UNSUR-UNSUR INTRINSIK CERPEN âá¸¤ÄDIá¹ AHâ DALAM ANTOLOGI DUNYAL-LÄH KARYA NAJÄªB MAá¸¤FÅªáº: ANALISIS STRUKTURAL-ROBERT STANTON - , RETNO TYAS HAPSARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to find out the intrinsic elements in short story âá¸¤Ädiá¹¡ahâ and the relation among them. The theory applied in this research is Stanton-structural theory with structural analysis-method. The problems discussed in this research are the intrinsic elements in the short story and the relation among them based on the Stanton-structural theory. The analyzed elements are theme, characters, plot, setting, point of view, title, and the relation among them in the work. The result of this research shows that the theme of the short story is lonely in facing heavy illness and life problem make many person feel desperate and suicide his self. The main character who plays the theme is an old man. In the story, he was suffering in severe illness and the cure given by doctors couldnât recovery him. Then he deliberately crossed the street when there were a car which high speed. The plot used in this short is mixed plot, the setting of place in this story are telephon booth, a highway interchange, Damradasy hospital